Punishing the Poor Through Welfare Reform: Cruel and Unusual? - Kendrex, Jennifer E.K. (1994)
This Comment aims to show how the Eighth Amendment intersects with welfare reform and what constitutional limits exist vis-à-vis welfare restrictions for society’s neediest citizens. Part I explores Eighth Amendment jurisprudence and its historical underpinnings and will provide background on the 1996 welfare reforms. Part II explores whether welfare reforms penalize individuals for their status as “poor” or “unemployed” and whether this constitutes cruel and unusual punishment. Finally, Part III illustrates how welfare programs can be reformed for constitutional compliance